The Influence Of Stimulus And Coping Mechanism To Hiv/Aids Patient Adaptation Based On Callista Roy Theory In Regional Public Hospital Kota Probolinggo - Dodik Hartono; Tintin Sukartini; Ima Nadatien (Alma Ata University Press, 2018)
HIV/AIDS patients experienced various problems that reviewed of adaptation models such as physical, psychological, social and dependency problems. The adaptation process can be influenced by stimulus and coop mechanism, one of stimulus which appear to HIV/AIDS client is negative stigma from the community, the surrounding environment and family rejection. The research objective is to analyze the effect of stimulus and coping mechanism to HIV / AIDS patient adaptation based on Callista Roy theory in regional public hospital Kota Probolinggo. The design of this study is correlation with the cross-sectional approach l. The populations are 68 respondents; the sample size of 58 respondents was taken by purposive sampling technique. This research instrument used a questionnaire; Data was analyzed using path analysis. The results showed that 1) Focal stimulus influences coping cognate (p = 0,000). Contextual stimulus affect coping regulator (p = 0,047) and coping cognate (p = 0,000). Residual stimulus affect coping cognate (p = 0,004). 2) Coping regulator affected about physiological adaptation (p = 0,006), role function adaptation (p = 0,040), interdependent adaptation (p = 0,004). Coping cognate affected physiological adaptation (p = 0,006), self-concept adaptation (p = 0,000), role function adaptation (p = 0,000), interdependent adaptation (p = 0,008). As a result of focal, contextual and residual stimulus, so that it forms coping cognate mechanism and produce four components of adaptation (physiological, self-concept, role function, interdependent) to HIV/AIDS patient. There needs to be an increase in coping cognate mechanisms to form four components of good adaptation, by giving counseling and mentoring to families and HIV/AID patient. Keyword : Stimulus, Coping Mechanism, Adaptation, HIV/AID